2020
DOI: 10.1111/jphd.12401
|View full text |Cite
|
Sign up to set email alerts
|

Availability of public dental care service and dental caries increment in children: a cohort study

Abstract: Objective: Evaluate the impact of the availability of public dental care service on the increment of dental caries in children. Methods: This is a 2-year cohort study that followed preschool children from southern Brazil. Dental caries was measured at baseline and follow-up evaluation, considering the number of surfaces with untreated dental caries. Demographic and socioeconomic characteristics as well as the use and availability of dental services were assessed. Multilevel Poisson regression analysis through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some aspects need also to be addressed to explain the incidence of dental caries. A factor that can impact the incidence of caries is the availability and access to dental services, as demonstrated in previous studies [Harris, 2016;Moraes et al, 2020]. Both the amount and quality of care provided are inversely related to the need, as proposed by the Inverse Care Law [Harris, 2016].…”
Section: Discussionmentioning
confidence: 97%
“…Some aspects need also to be addressed to explain the incidence of dental caries. A factor that can impact the incidence of caries is the availability and access to dental services, as demonstrated in previous studies [Harris, 2016;Moraes et al, 2020]. Both the amount and quality of care provided are inversely related to the need, as proposed by the Inverse Care Law [Harris, 2016].…”
Section: Discussionmentioning
confidence: 97%
“…It is possible to unavailable facilities to provide treatments for dental caries of children. However, a cohort study conducted in Southern Brazil has revealed that availability of public dental care reduces the untreated dental caries in children as it increased the accessibility (Moraes et al, 2021) [10] . In this rural Sri Lankan group of children oral health care utilization might be affected by many factors which are not investigated in this study, demonstrating no association between untreated dental caries and availability of oral health care.…”
Section: Resultsmentioning
confidence: 99%
“…Occupation, parental schooling, and low family income were identified as predisposing factors for dental caries in children and adolescents (López et al, 2006; Peres et al, 2005). DMFT, being such a mediator, could rely on the socioeconomic influence of access to dental care, as well as behavioral factors (Moraes et al, 2020; Vettore et al, 2019).…”
Section: Discussionmentioning
confidence: 99%